(3bQGQGJ fRY GdedcjI ddefaYI GdYGeI hGdQbGHI GdbVGFjI YdjgG ai Gdjef (B: s (3OQGS`I ebGQfI (B/ s - (3CHgG YHOGddg HGMWGHs; (3LGHQ LGO fUGQ (B: s ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI , s, 2015)
(3jYJHQ ehVhY fRY GdedcjI ef GdehVhYGJ GdeJQGHWI hGdeJTYHI hGdJj JONd aj GNJUGU CcKQ ef bGfhf haj faS GdhbJ JSJbd HPGJgG(B: (3afLOgG aj GdbGfhf GdeOfj hGdEOGQj(B: (3ceG CfgG JQJHW HehVhY GdCehGd GdYGeI(B: (3JMJGL CMjGfkG dbGfhf GdeQGaYGJ(B: (3hfLOgG aj bhGfjf eNJdaI hGdGge ef cd Pdc dgG JfXje bGfhfj NGU HgG (B- (3bGfhf GdGSJedGc Ch fRY GdedcjI ddefaYI GdYGeI (B- (3jfXe CehQgG GdafjI hGdELQGFjI ceG jHjf cjajI GdJYhjV hZjQgG ef GdehGVjY PGJ GdUdI(B. (3hJcef CgejI gPG GdehVhY HGYJHGQg jeS HMb GdedcjI GdNGUI GdJj JcadgG GdJTQjYGJ GdSeGhjI bHd GdbhGfjf GdhVYjI(B: (3gPG ef LgI(B: (3hef LgI CNQi jJYdb gPG GdehVhY HJMbjb efaYI gGeI(B: (3hceG gh eYdhe aEf GdefGaY GdYGeI JbOe Ydi GdeUGdM GdNGUI(B: (3Cj CffG dGHO ef Cf fMbb GdJhGRf eG Hjf JfajP eTGQjY PGJ faY YGe hMeGjI Mbhb GdedcjI GdNGUI HGdCaQGO(B. (3hMJi jJMbb gPG GdJhGRf dGHO ef Cf fbhe HOQGSI ehVhY fRY GdedcjI ef cGaI LhGfHg(B: (3hYdjg befG HOQGSI GdTQhW GdhGLH JhGaQgG ai YedjI fRY GdedcjI (B: (3h YedfG Ydi GdJejjR eG Hjf YedjI fRY GdedcjI h ZjQgG ef GdJUQaGJ GdEOGQjI GdeTGHgI dgG(B: (3hGdJj bO jdJHS Ydi GdHYV GdJaQjb HjfgG(B. s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGes
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdEOGQjs; (3GdJUQaGJ GdEOGQjIs; (3bGfhf GdGSJedGc s; (3fRY GdedcjI s; (3QSGFd LGeYjI s -- (3LGeYI GdbGgQI s -- (3cdjI GdMbhb s